Fitness Model of Physical Activity/Exercise During the Home Stay Period of COVID-19 - Rafiq, Muhammad Tariq (Journal of Liaquat University of Medical & Health Sciences, 2021)
The COVID-19 pandemic was first detected in China at the end of 20191. Today, the COVID-19 is the biggest public health issue that is challenging the world2. World Health Organization has advised people to stay at home as a safety recommendation and precaution to reduce the transmission and exposure of the virus3. It is necessary to prevent the virus from spreading by quarantine and social distancing. People feel loneliness and social isolation by the safety recommendations of the virus. Both loneliness and social isolation produce physical and mental-health-related problems. Low levels of physical activity and sitting for a long time are risk factors for disease development.